Implementasi Kebijakan Perizinan Kegiatan Masyarakat Pada Kepolisian Daerah Jawa Timur - Maharani, Raysha Aulia; Anisykurlillah, Rosyidatuzzahro (Innovative: Journal Of Social Science Research, 2025)
This study analyzes the implementation of the Community Activity Licensing Policy in the East Java Regional Police, which plays an important role in maintaining security and order amidst various community activities, including arts and entertainment. The licensing process involves dispositions from superiors to subordinates, evaluations and final decisions from the director with the aim of ensuring transparency and accountability. Although the policy is running according to the rules, there are obstacles that affect the effectiveness of its implementation, such as communication, human resources, and adequate infrastructure. This study emphasizes the importance of integrating all activities in a responsive police service system to improve the effectiveness of public services. The results of the study show that although there are challenges in licensing, the police strive to provide good service and maintain security during the activities.